Implementation of PhET Simulation on Motion Material to Improve Problem Solving Skills of Middle School Students - Nur Hidayati; Munasir Munasir; Mita Anggaryani; Muhammad Satriawan (Postgraduate, University of Mataram, 2025)
This study aimed to enhance junior high school students’ problem-solving skills through the integration of PhET simulations within a Problem-Based Learning (PBL) model. The research design employed was Classroom Action Research (CAR), carried out in two iterative cycles consisting of planning, implementation, observation, and reflection stages. A total of 60 Grade VII students from two parallel classes at a private junior high school in Surabaya participated in this study during the 2024–2025 academic year. Data collection involved pre-tests and post-tests for each cycle, focusing on both general learning outcomes and specific indicators of problem-solving ability. The data were analyzed quantitatively using the normalized gain (N-Gain) formula. Results showed that general learning outcomes improved from an N-Gain score of 0.29 in the first cycle (low category) to 0.69 in the second cycle (medium category). Problem-solving skills demonstrated a stronger gain, increasing from 0.47 (medium) to 0.85 (high). These improvements suggest that combining differentiated instruction and simulation-based learning effectively fosters students’ conceptual understanding and higher-order thinking. The study concludes that the PhET-assisted PBL approach is a promising instructional model to develop both cognitive and analytical competencies in science education, particularly in motion and force topics.